Analisis Yuridis Kebijakan Baru Ditjen AHU Terkait Dokumen Tambahan dalam Pendaftaran Perubahan Yayasan oleh Notaris - Riris Cahaya Andini; Lutfia Brillian Arysa Mungky; Nisa Almadina (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the juridical implications of the new policy of the Directorate General of General Legal Administration (Ditjen AHU) regarding the requirements for additional documents in the registration of changes in foundation data by notaries. The background of this study was triggered by an administrative renewal of the system aimed at tightening institutional verification and preventing internal disputes of the foundation, which in turn put a new burden of obligation on notaries as public officials. Using normative legal research methods through legislative approaches and conceptual approaches, this study examines secondary legal materials that include ministerial regulations and related circulars. Research results show that the obligation to upload additional documents, such as affidavits not in dispute and corporate account renewal, changes standard procedures on the online AHU system. Although this policy succeeded in increasing the validity of the data and strengthening legal certainty, this new regulation also added bureaucracy and shifted the burden of substantive verification more heavily to notaries. The implications of this study confirmed the need for the Ministry of Law to balance between the firmness of administrative supervision and the efficiency of the system, to ensure that electronic portals remain accommodating while minimizing the risk of office responsibility for notaries.